AKULTURASI ISLAM DAN BUDAYA LOKAL: ANALISIS NILAI-NILAI FILOSOFIS TRADISI PENYAMBUTAN KEPULANGAN HAJI DAN RITUAL TASYAKURAN - Mohammad Rifai; Moh Farid Ridlo Rofii (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The tradition of welcoming returning Hajj pilgrims and the accompanying thanksgiving rituals in Indonesia are not merely sociological phenomena of geographical relocation; rather, they represent a cultural space laden with the dialectic of acculturation between Islamic orthodoxy and local traditions. This study aims to radically dissect the varieties of cultural nuances, the models of religious-cultural hybridization, and the philosophical values embedded within the Hajj homecoming celebrations and thanksgiving rituals (walimatun naqi’ah). Employing a descriptive qualitative method enhanced by a comparative ethnographic approach, this study analyzes three primary regional focuses as descriptive loci, namely the welcoming traditions in Java, Madura (asajere), and Bugis-Makassar (mappatoppo). The findings conclude that this tradition embodies a harmonious integration manifested into three substantive philosophical values: (1) A theological-spiritual transformation from individual piety toward becoming agents of social piety; (2) The recreation and reinforcement of communal social capital to reduce polarization; and (3) The existence of cultural expressions of gratitude that manifest the theory of the indigenization of Islam (Pribumisasi Islam) in the Indonesian Archipelago. This research implies a strengthening of the literature in the anthropology of religion regarding the flexibility of theological Islamic doctrines when adapting to local Nusantara cosmologies without uprooting the essence of tawhid (monotheism).